1993
DOI: 10.1172/jci116732
|View full text |Cite
|
Sign up to set email alerts
|

Triamcinolone and prednisolone affect contractile properties and histopathology of rat diaphragm differently.

Abstract: Diaphragm atrophy and weakness occur after administration of massive doses of corticosteroids for short periods. In the present study the effects of prolonged administration of moderate doses of fluorinated and nonfluorinated steroids were investigated on contractile properties and histopathology of rat diaphragm. 60 rats received saline, 1.0 mg/kg triamcinolone, or 1.25 or 5 mg/kg i.m. prednisolone daily for 4 wk. Respiratory and peripheral muscle mass increased similarly in control and both prednisolone grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
63
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 33 publications
6
63
0
1
Order By: Relevance
“…Glucocorticoid-induced myopathy is characterized by a decrease in the size of muscle fibers (13). In the present study, glucocorticoid treatment caused a 31% decrease in mean muscle fiber CSA of TA muscle compared to controls.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Glucocorticoid-induced myopathy is characterized by a decrease in the size of muscle fibers (13). In the present study, glucocorticoid treatment caused a 31% decrease in mean muscle fiber CSA of TA muscle compared to controls.…”
Section: Discussionsupporting
confidence: 50%
“…Second, the present study did not measure muscle fiber CSA based on muscle fiber phenotype, as TA muscle in rats is almost exclusively composed of type II fibers. Although glucocorticoids are known to cause muscle atrophy of fast-twitch (type II) muscle fibers (13), the effects of glucocorticoids on muscle fiber phenotypes in other muscles should be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no doubt that the relationship between steroid treatment and muscle weakness may be causal. Indeed, numerous animal studies have demonstrated a causal relationship between steroid treatment and muscle weakness [34,36]. Following this hypothesis, enhanced complaints would lead both to hospital admission and steroid treatment, with consequent muscle weakness.…”
Section: Discussionmentioning
confidence: 99%